RIFM fragrance ingredient safety assessment, elemol, CAS Registry Number 639-99-6. (December 2017) - Api, A.M.; Belsito, D.; Bhatia, S.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Calow, P.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: Elemol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using target data and/or TTC.